Controls for election and candidacy in Jordanian legislation and comparative legislation - Altorah, Jad Hamad; Al Khattab, Khamis Abed Rabu; Al-Humaidat, Abdullah khader (Journal of Economic, Administrative and Legal Sciences, 2021)
Parliamentary elections are the best way to assign power in democratic systems, and when individuals elect members of parliament, they choose whoever represents the nation in exercising some aspects of sovereignty by setting appropriate legislation for the nation on the one hand, and monitoring government actions issued by the executive authority on the other hand, and from that. The justification for individuals' submission to authority becomes clear, which leads to political harmony and stability.This research aims to study the controls of this right as stipulated in international charters and the constitutions of some countries, and then discuss how the successive Jordanian constitutions have dealt with this right and the subsequent legislations and ordinary laws, and in its endeavor to identify the extent to which Jordanian constitutions and legislation enable the promotion and protection of the right to vote and run. The study concluded that the Jordanian constitution took into account the most important principles and foundations related to this right by stipulating them in the body of the constitution, as did the Jordanian legislation governing the right to vote.
Keywords: regulations; election; constitution; candidacy; allocated seats